The mental health impact of COVID-19 pandemic in indonesian older people: the implication for sleep deprivation, loss of appetite, and psychosomatic complaints - Nugraha, Susiana; dawiyah, Asyifa Robiatul; Aprillia, Yuna Tricusi; Agustina, Lisna; Handayani, Tresna Putri Asih; Rahardjo, Tri Budi Wahyuni (Jurnal Ners, 2022)
Background : During the COVID-19 pandemic, many individuals were concerned about being infected. Meanwhile, the elderly felt isolated due to the detrimental effect on their mental and physical health. Therefore, this study aimed to identify the mental health issues suffered by the elderly during the COVID-19 pandemic. The most frequent mental health issues assessed are sleep deprivation, loss of appetite, and psychosomatic complaints.Method : This is a descriptive-analytic study using a cross-sectional approach to find the mental health impact of the COVID-19 pandemic. The population consists of 259 older adults (â‰¥60 years) living in West Java and Jakarta.Results : The average age of study participants is 65.3 years old (±6.8SD range 60–89 years old). The multivariable logistic regression model showed that sleep deprivation is signifantly associated with non-college education background (OR=2.28;95%CI; 1.23-4.61), anxiety (OR=7.09; 95%CI; 3.57-14.08), and the existence of chronic illness (OR=2.75; 95%CI; 1.44 -5.26). Subsequently, the psychosomatic symptom was associated with anxiety (OR=5.27; 95%CI; 2.75 -10.11) and chronic illness (OR=2.80; 95%CI; 1.47 -5.32). Loss appetite was associated with non-college education background (OR=2.50; 95%CI; 1.16-5.41), anxiety (OR=10.41; 95%CI; 5.01-21.63), and the existence of chronic illness (OR=3.60; 95%CI; 1.72-7.55). The analysis showed that none of the COVID-19 related fear is associated with a sleep disorder, loss of appetite, and psychosomatic symptoms.Conclussion : A psychosocial approach is necessary to reduce the mental health issues during the Covid-19 Pandemic, focusing on anxiety management and assisting those with chronic diseases and low education.